A new micro‐furnace for in situ high‐temperature single‐crystal X‐ray diffraction measurements. (1st August 2015) - Alvaro, M.; Angel, R. J.; Marciano, C.; Milani, S.; Scandolo, L.; Mazzucchelli, M. L.; Zaffiro, G.; Rustioni, G.; Briccola, M.; Domeneghetti, M. C.; Nestola, F.
<x xml:space="preserve">Abstract</x> A new micro‐furnace equipped with an H‐shaped resistance heater has been developed to conduct in situ single‐crystal X‐ray diffraction experiments at high temperature. The compact design of the furnace does not restrict access to reciprocal space out to 2θ = 60°. Therefore, unit‐cell parameters and intensity data can be determined to a resolution of 0.71 Å with Mo radiation. The combined use of mineral phases with well characterized lattice expansion (e.g. pure Si and SiO2 quartz) and a small‐diameter (0.025 mm) K‐type thermocouple allowed accurate temperature calibration from room temperature to about 1273 K and consequent evaluation of thermal gradients and stability. The new furnace design allows temperatures up to about 1273 K to be reached with a thermal stability better than ±5 K even at the highest temperatures. Measurements of the lattice thermal expansion of pure silicon (Si), pure synthetic grossular garnet (Ca3Al2Si3O12) and quartz (SiO2) are presented to demonstrate the performance of the device. Its main advantages and limitations and important considerations for using it to perform high‐temperature diffraction measurements are discussed.